Discrimination power of knowledge testing items - Krylovas, Aleksandras; Kosareva, Natalja; Karaliūnaitė, Julija (Lietuvos matematikos rinkinys, 2017)
In the article one fuzzy classification algorithm of dichotomous test questions is proposed. Depending on the level of knowledge measured by the test, the test item for example may well differentiate whether all testees or only testees with strong or only with weak level of knowledge; as well as the test item may badly differentiate testees and therefore be inappropriate. In the research fuzzy sets mathematical theory is used.